Association Between ALDH-2 rs671 and Essential Hypertension Risk or Blood Pressure Levels: A Systematic Review and Meta-Analysis - Zheng, Yawei; Ning, Cheng; Zhang, Xingxing; Zhao, Yuhao; Li, Yizhuo; Qian, Lichao; Li, Jie; Fang, Zhuyuan (Frontiers in Genetics, 2020)
Background: The association between Aldehyde dehydrogenase Ⅱ (ALDH-2) rs671 polymorphism and essential hypertension (EH) risk or blood pressure (BP) variation remains unclear. Objective: To systematically review the influence of the aldehyde dehydrogenase Ⅱ rs671 polymorphism on essential hypertension risk and blood pressure variation. Methods: The PubMed, EMbase, Web of Science, Cochrane Library, CNKI and CBM databases were electronically searched to identify case-control or cohort studies published prior to July 2019 that examined the association between the rs671 polymorphism and the risk of essential hypertension or blood pressure variation. A meta-analysis was conducted with Stata 15.1 software. Results: Twenty-two articles were included. Among these articles, 20 incorporated 30 individual studies evaluating the association between the rs671 polymorphism and EH, and 8 incorporated 12 individual studies evaluating the association between the rs671 polymorphism and BP. The results of the meta-analysis showed that the mutation of the rs671 polymorphism was associated with a significantly decreased risk of EH in all models: allelic model (OR=0.80, 95% CI: 0.73-0.87), homozygous model (OR=0.71, 95% CI: 0.63-0.80), heterozygous model (OR=0.79, 95% CI: 0.72-0.87), dominant model (OR=0.79, 95% CI: 0.71-0.87), and recessive model (OR=0.76, 95% CI: 0.68-0.85). In the stratified analyses, significant associations were found for males, drinkers and population-based studies. Simultaneously, the A carriers had lower SBP (WMD=-1.78, 95% CI: -3.02 to -0.53) and DBP (WMD=-1.09, 95% CI: -1.58 to -0.61) levels than individuals with the GG homozygote. Conclusion: The collective findings of this meta-analysis suggested that the ALDH-2 rs671 polymorphism represented an important genetic marker in the development of hypertension. Considering the overall quality of evidence and the relatively small pooled sample size, more well-conducted high-quality studies are required to verify the above conclusion.